English Deutsch Français Italiano Español Português 繁體中文 Bahasa Indonesia Tiếng Việt ภาษาไทย
All categories

Find dy/dx of:

y = (ln(x^2))^(2x+3)

2006-11-01 14:28:19 · 1 answers · asked by Anonymous in Science & Mathematics Mathematics

1 answers

y = (ln x²)^(2x+3) = e^((2x+3) ln ln x²)
Now just ruthlessly apply the chain rule:
dy/dx = e^((2x+3) ln ln x²) * (2 ln ln x² + (2x+3) * 1/ln x² * 1/x² * 2x)
And simplify:
(2 ln x)^(2x+3) * (2 ln (2 ln x) + (2x+3)/(x ln x))

2006-11-01 14:45:28 · answer #1 · answered by Pascal 7 · 0 0

fedest.com, questions and answers